(untitled) (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: Blood lipid levels differently impact ischemic stroke and hemorrhagic stroke. The effect of acute illness on lipid metabolism may alter lipid levels after acute stroke. Objectives: To measure the fasting lipid profile after acute stroke and to compare between ischemic and hemorrhagic stroke. Methods: This cross-sectional study enrolled 247 acute stroke patients (112 hemorrhagic and 135 ischemic; age 59.7 (±13.4) years, 48.6% female) from a referral neuroscience hospital in Dhaka, during February-June 2021. Fasting lipid profile was measured by enzymatic [total cholesterol (TC)], accelerator selective detergent [both high-density lipoprotein cholesterol (HDL-c) and low-density lipoprotein cholesterol (LDL-c)], and glycerol phosphate oxidase method [triglyceride (TG)] by the Abbott Alinity system. Elevated TC, TG and LDL-c were defined as ≥200 mg/dL, ≥150 mg/dL and ≥130 mg/dL respectively while low HDL-c as <40 mg/dL. Presence of either elevated serum TC, TG, LDL-c or low HDL-c was regarded as dyslipidemia. Results: Dyslipidemia was present in 70.9% (175 of 247) with similar frequency in stroke subtypes (p=0.221). Both TC and HDL-c were low in ischemic stroke in comparison to hemorrhagic stroke (p=0.017 and p=0.042 respectively). TG and LDL-c were similar between two groups (p=NS for both). Frequency of low HDL-c was higher in ischemic stroke (p=0.034) but no significant difference in frequency of elevated TC, TG, LDL-c between two groups. There was a higher TG/HDL-c ratio in ischemic stroke in comparison to hemorrhagic stroke (p=0.003), but TC/HDL-c and LDL-c/HDL-c ratio was similar. When the characteristics of the participants with or without dyslipidemia were compared within two stroke types, only the frequency of diabetes was higher in ischemic stroke with dyslipidemia in comparison to those who had no dyslipidemia (p=0.005). Conclusions: Dyslipidemia is frequent in acute stroke. The fasting TC and HDL-c are low and TG/HDL-c is high in ischemic stroke in comparison to hemorrhagic stroke. J Assoc Clin Endocrinol Diabetol Bangladesh, July 2023; 2 (2):52-57